The Analysis of English Teachers Teaching Style and Their Effect on Students Interest at SMP Negeri 3 Sorong City - Peter Manuputty; Lusia Hadia; Agustinus Lia Masan (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The objective of the research (1) the teaching styles applied by the English teachers at SMP N 3 Sorong City (2) the effects of English teachers teaching styles on students’ interest in learning at SMP N 3 Sorong City. This research uses Descriptive qualitative method. Subject of this research are seventh grade, eighth grade and ninth grade of SMPN 3 Sorong City. Respondents consisted of 3 English teachers and six students. The data gathered through observation, interview and documentation. The results of this research showed that (1). The English teacher at SMPN 3 Sorong City applied 3 teaching style namely expert formal authority, and facilitator (2) the researcher elaborated student’s interest into 5 categories which are based on Slameto theory are attention, willingness, feeling happy, teaching materials and teachers’ attitude and participation.